General Andrew Wauchope of Niddrie Marischal. A character sketch and brief historical tribute - McPherson, Eric (Scientia Militaria - South African Journal of Military Studies, 2012)
Two months after the outbreak of the Anglo-Boer War a series of battles took place which shook Britain. These were Stormberg (10 December1899), Magersfontein (11 December 1899) and Colenso (15 December 1899). All had been reverses for the British army and had taken place within a week which became known as Black Week - a phrase coined by the British Liberal Party politician Asquith. Great Britain was regarded as having the world’s most powerful army at the time and the losses suffered against the Boers resulted in humiliation and anguish for the British nation. However, nowhere was the anguish greater than in Scotland for at Magersfontein the Highland Brigade had fared badly suffering severe losses including their commander, Major-General Andrew Wauchope, killed in action. As Conan Doyle put it, "Never has Scotland had a more grievous day than this at Magersfontein. She had always given her best blood with lavish generosity for the Empire, but it may be doubted if any single battle has ever put’ so many families of high and low, into mourning from the Tweed to Caithness shore." (Doyle, 1900:24) In the words of biographer William Baird "the empire has lost one of its noblest and best, a hero has gone down to his rest ere his full life’s work was done". (Baird, 1902:196) Although these statements may seem somewhat flowery and were expressed during a period of much patriotic fervour, they nevertheless indicate the emotional reaction to Andrew Wauchope’s untimely death.